Using Symbolism to Develop The Themes of George Orwell’s 1984 - Mekaddem, Soumia Badr; Koreichi, Souhila (Faculty of Letters and Foreign Languages Department of English, 2018)
The target of this research paper is to explore the symbols used as a part of the novel and to decode these symbols as well as distinguish the different interpretations they stand for, then linking them to themes which they develop. The study hypotheses that George Orwell might use symbols to add an aesthetic value to this novel. Each symbol has a special interpretation and certain significance. Also, he might use symbols to express his own views and each could have a connection with a particular theme of the novel. After analyzing the novel, the study concluded that Orwell uses symbols to convey his warning message against totalitarian rule and to develop the themes of his novel